Quantification and variability in colonic volume with a novel magnetic resonance imaging method. Issue 12 (10th September 2015) - Nilsson, M.; Sandberg, T. H.; Poulsen, J. L.; Gram, M.; Frøkjær, J. B.; Østergaard, L. R.; Krogh, K.; Brock, C.; Drewes, A. M.
Abstract: Background: Segmental distribution of colorectal volume is relevant in a number of diseases, but clinical and experimental use demands robust reliability and validity. Using a novel semi‐automatic magnetic resonance imaging‐based technique, the aims of this study were to describe: (i) inter‐individual and intra‐individual variability of segmental colorectal volumes between two observations in healthy subjects and (ii) the change in segmental colorectal volume distribution before and after defecation. Methods: The inter‐individual and intra‐individual variability of four colorectal volumes (cecum/ascending colon, transverse, descending, and rectosigmoid colon) between two observations (separated by 52 ± 10) days was assessed in 25 healthy males and the effect of defecation on segmental colorectal volumes was studied in another seven healthy males. Key Results: No significant differences between the two observations were detected for any segments (All p   >  0.05). Inter‐individual variability varied across segments from low correlation in cecum/ascending colon (intra‐class correlation coefficient [ICC] = 0.44) to moderate correlation in the descending colon (ICC = 0.61) and high correlation in the transverse (ICC = 0.78), rectosigmoid (ICC = 0.82), and total volume (ICC = 0.85). Overall intra‐individual variability was low (coefficient of variance = 9%). After defecation the volume of the rectosigmoid decreased by 44% ( p  = 0.003). The change in rectosigmoid volume was associated with the true fecal volume ( p  = 0.02). Conclusions & Inferences: Imaging of segmental colorectal volume, morphology, and fecal accumulation is advantageous to conventional methods in its low variability, high spatial resolution, and its absence of contrast‐enhancing agents and irradiation. Hence, the method is suitable for future clinical and interventional studies and for characterization of defecation physiology. Abstract : Segmental colorectal volumes assessed on two separate occasions exhibit low intra‐individual and inter‐individual variability in healthy human volunteers when assessed with this novel MRI‐based software. The method is sensitive to the changes in colorectal volume distribution that occur after defecation and because the software is semi‐automatic the time expenditure is greatly reduced.